Group Exhibition-erra Vita Xiamen, Chinese European Art Center, Xiamen - Antoniou, Klitsa (My University, 2026)
Terra Vita Xiamen, Chinese European Art Center, Xiamen, China, Curated by Ineke Gudmandson